β-cell metabolism, insulin production and secretion: Metabolic failure resulting in diabetes - Chen, Y.; Cruzat, Vinicius; Newsholme, P. (Wiley - V C H Verlag GmbH, 2016)
Located in the islets of Langerhans of the pancreas, β cells perform essential hormone secretory functions that affect metabolism. Nutrients are potent regulators of β-cell insulin secretion, which is essential to the organism. In the past few decades, changes in lifestyle, especially related to overnutrition, has increased the global incidence of obesity-associated diabetes. In this scenario, impairment to β-cell function may lead to failure and gradual progression to type 2 diabetes. Multiple molecular pathways have been identified that contribute to dysfunction associated with glucotoxicity and lipotoxicity. Recent in vitro and in vivo studies have led to a better understanding of the complexities of β-cell dysfunction and how it interferes in the pathways of insulin secretion and action. New therapeutic strategies targeting the molecules sensitive and responsive to cell nutrition in the context of diabetes present new opportunities and are presented in the present chapter.